Implementasi Data Warehouse Pada Pengelolaan Sampah Digital Tingkat Kelurahan Di Jakarta Selatan - Nurzaman, Adam Fahsyah; Alexander, Dennis (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The serious issue of waste management in Indonesia, particularly in Jakarta, with an average of 7500 tons of waste received daily by the Bantargebang Integrated Waste Processing Facility, has prompted efforts to reduce pollution through the concept of waste banks employing the 3R (Reduce, Reuse, Recycle) approach. However, observations at waste banks in South Jakarta have revealed challenges in transaction recording, which are often difficult to address by waste bank administrators, ranging from input errors to reports that do not meet stakeholders' expectations. In this context, this research proposes the implementation of a data warehouse for more flexible and accessible information presentation to waste bank administrators and stakeholders. The outcomes encompass data warehouse's ability to provide better insights into the daily, weekly, monthly, and yearly developments and financial impacts of waste banks, along with data visualization in the form of graphs and dashboards, potentially offering significant support for more efficient and sustainable waste management efforts in South Jakarta.